Ø§Ù„Ø¯Ø±Ø³Ø© Ø§Ù„ÙƒÙˆ ÙÙŠØ© ÙˆØ§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù†ØÙˆ Ù‰ Ù…Ù†Ù‡Ø§ - Asdari, ÙA (Buletin Al-Turas, 2009)
In the study of the science of nahwu and saraf (Arabic grammer) there exist two opposing schools of thoughts, namely the school of Basrah wich came earlier and the school of Kufah wich appeared after that. The school of Kufah Determine Arabic vocabularies through what they believe originated from verbs. Whereas the School of Kufah determine Arabic Vocabularies through what they have heard from their ancestors wether through poems, prose, and others thus not needing a definite principle as is adopted by the School of Basrah.